Capillary Proliferation in Systemic‐Sclerosis‐Related Pulmonary Fibrosis: Association with Pulmonary Hypertension. Issue 1 (15th March 2019) - Seki, Atsuko; Anklesaria, Zafia; Saggar, Rajeev; Dodson, Mark W.; Schwab, Kristin; Liu, Ming‐Chang; Charan Ashana, Deepshikha; Miller, William D.; Vangala, Sitaram; DerHovanessian, Ariss; Channick, Richard; Shaikh, Faisal; et al.
Abstract : Objective: We sought to determine if any histopathologic component of the pulmonary microcirculation can distinguish systemic sclerosis (SSc)‐related pulmonary fibrosis (PF) with and without pulmonary hypertension (PH). Methods: Two pulmonary pathologists blindly evaluated 360 histologic slides from lungs of 31 SSc‐PF explants or autopsies with (n = 22) and without (n = 9) PH. The presence of abnormal small arteries, veins, and capillaries (pulmonary microcirculation) was semiquantitatively assessed in areas of preserved lung architecture. Capillary proliferation (CP) within the alveolar walls was measured by its distribution, extent (CP % involvement), and maximum number of layers (maximum CP). These measures were then evaluated to determine the strength of their association with right heart catheterization–proven PH. Results: Using consensus measures, all measures of CP were significantly associated with PH. Maximum CP had the strongest association with PH ( P = 0.013; C statistic 0.869). Maximum CP 2 or more layers and CP % involvement 10% or greater were the optimal thresholds that predicted PH, both with a sensitivity of 56% and specificity of 91%. The CP was typically multifocal rather than focal or diffuse and was associated with a background pattern of usual interstitial pneumonia. There was a significant but weaker relationship between the presence of abnormal small arteries and veins and PH. Conclusion: In the setting of advanced SSc‐PF, the histopathologic feature of the pulmonary microcirculation best associated with PH was capillary proliferation in architecturally preserved lung areas.